Correction: Mek1 Down Regulates Rad51 Activity during Yeast Meiosis by Phosphorylation of Hed1. - Tracy L Callender; Raphaelle Laureau; Lihong Wan; Xiangyu Chen; Rima Sandhu; Saif Laljee; Sai Zhou; Ray T Suhandynata; Evelyn Prugar; William A Gaines; YoungHo Kwon; G Valentin Börner; et al. (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1006226.].